Unexpected diversity found within benthic microbial mats at hydrothermal springs in Crater Lake, Oregon - Stromecki, Amanda; Murray, Laura; Fullerton, Heather; Moyer, Craig L. (Frontiers in Microbiology, 2022)
Crater Lake, Oregon is an oligotrophic freshwater caldera lake fed by thermally and chemically enriched hydrothermal springs. These vents distinguish Crater Lake from other freshwater systems and provide a unique ecosystem for study. This study examines the community structure of benthic microbial mats occurring with Crater Lake hydrothermal springs. Small subunit rRNA gene amplicon sequencing from eight bacterial mats were used to assess community structure. These revealed a relatively homogeneous, yet diverse bacterial community. High alpha diversity and low beta diversity indicates that these communities are likely fueled by homogeneous hydrothermal fluids. An examination of autotrophic taxa abundance indicates the potential importance of iron and sulfur inputs to the primary productivity of these mats. Chemoautotrophic potential within the mats was dominated by iron oxidation from Gallionella and Mariprofundus and by sulfur oxidation from Sulfuricurvum and Thiobacillus with an additional contribution of nitrite oxidation from Nitrospira. Metagenomic analysis showed that cbbM genes were identified as Gallionella and that aclB genes were identified as Nitrospira, further supporting these taxa as autotrophic drivers of the community. The detection of several taxa containing arsC and nirK genes suggests that arsenic detoxification and denitrification processes are likely cooccurring in addition to at least two modes of carbon fixation. These data link the importance of the detected autotrophic metabolisms driven by fluids derived from benthic hydrothermal springs to Crater Lake’s entire lentic ecosystem.